Potential neuroprotective effect of lithium in bipolar patients evaluated by neuropsychological assessment: preliminary results. (13th November 2015) - Bersani, Giuseppe; Quartini, Adele; Zullo, Daiana; Iannitelli, Angela
Abstract : Objective: Accumulating evidence is delineating a neuroprotective/neurotrophic role for lithium. However, its primary effects on cognition remain ambiguous. We sought to investigate the profile of cognitive impairment in patients with bipolar disorder and to determine whether continued treatment with lithium preserves cognitive functioning. Methods: In this cross‐sectional study, we tested 15 euthymic patients with bipolar I disorder undergoing long‐term clinical maintenance treatment with lithium (for at least 12 months), 15 matched patients treated with other mood‐stabilizing drugs and who had never received lithium, and 15 matched healthy subjects on the Cambridge Neuropsychological Test Automated Battery. Investigated cognitive domains were visual memory, executive functions, attention, decision‐making/impulsivity, and response inhibition. We controlled for age, gender, intelligence, and residual psychiatric symptomatology. Results: Taken together, bipolar patients demonstrated robust deficits in visual memory and executive functions. Once subdivided in treatment subgroups, only non‐lithium bipolar patients demonstrated impairments in visual memory. Attention, decision‐making, and response inhibition were preserved in both groups. No correlation emerged between neuropsychological tests performance, clinical, and psychological variables. Conclusions: This study is the first to our knowledge to have demonstrated, by means of a highly sensitive test of visual memory, a potential hippocampus neuroprotective effect of lithium in patients with bipolar disorder. Besides, it confirms prior findings of cognitive deficits in euthymic bipolar patients. Copyright © 2015 John Wiley & Sons, Ltd.